Optimized Antibiotic Management of Critically Ill Patients with Severe Pneumonia Following Multiplex Polymerase Chain Reaction Testing: A Prospective Clinical Exploratory Trial - Alexia Verroken; Julien Favresse; Ahalieyah Anantharajah; Hector Rodriguez-Villalobos; Xavier Wittebole; Pierre-François Laterre (Antibiotics, 2024)
Molecular diagnostic testing is assumed to enable fast respiratory pathogen identification and contribute to improved pneumonia management. We set up a prospective clinical trial at a tertiary hospital intensive care unit including adult patients suspected of severe pneumonia from whom a lower respiratory tract sample could be obtained. During control periods (CPs), routine testing was performed, and during intervention periods (IPs), this testing was completed with the FilmArray Pneumonia Panel plus test (FA-PNEU) executed 24/7. The main objective was to measure the impact of FA-PNEU results in terms of reduced time to targeted antimicrobial treatment administration. Over a 10-month period, analysis was performed on 35 CP and 50 IP patients. The median time to targeted antimicrobial treatment administration was reduced to 4.3 h in IPs compared to 26.4 h in CPs, with 54% of IP patients having FA-PNEU results that led to a treatment modification, of which all but one were targeted. Modifications included 10 (37%) de-escalations, 7 (25.9%) escalations, 3 (11.1%) regimen switches, and 7 (25.9%) complete antimicrobial discontinuations. FA-PNEU results were available with a 42.3 h gain compared to routine identification. This prospective study confirmed retrospective data demonstrating the benefit of FA-PNEU testing in severe pneumonia management of critically ill patients through improved antimicrobial use.